2021
DOI: 10.1007/s11136-021-02929-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and subjective sleep-related measures in bipolar disorder and major depressive disorder

Abstract: Purpose Diminished quality of life (QoL) has been reported in patients with mood disorders. QoL has also been shown to be decreased by sleep disturbances. Since sleep disorders are common in mood disorders, the aim of this study was to determine whether sleep characteristics are associated to QoL among patients with Bipolar Disorder (BD) and unipolar Major Depressive Disorders (MDD). Methods QoL was assessed in 170 patients with mood disorders (61 BD and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…For others it may be more associated with their mental health condition (for instance the indicated affective disorders and their correlation with sleep quality) 38 . Studies show association between quality of life and subjective sleep‐related measures in BD and major depressive disorder, however, when we add factors connected with T1DM control, this makes sleep disturbances even more prominent 39 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For others it may be more associated with their mental health condition (for instance the indicated affective disorders and their correlation with sleep quality) 38 . Studies show association between quality of life and subjective sleep‐related measures in BD and major depressive disorder, however, when we add factors connected with T1DM control, this makes sleep disturbances even more prominent 39 …”
Section: Discussionmentioning
confidence: 98%
“…38 Studies show association between quality of life and subjective sleep-related measures in BD and major depressive disorder, however, when we add factors connected with T1DM control, this makes sleep disturbances even more prominent. 39 Finally, we have examined the temperament traits distribution and severity in the examined population. We were searching for connections between trait severity, affective symptoms and metabolic control.…”
Section: Discussionmentioning
confidence: 99%
“…Although the complex or residual disease may also appear to develop HIV, people living with TB have never expected to experience severe TB symptoms similar to those with HIV. Community communication and awareness of TB may be lower than HIV [ 26 ]. Being non-Papuan with TB will be more resilient to cope with disability compared to Papuans.…”
Section: Discussionmentioning
confidence: 99%
“…These few studies have mostly focused on the presence or absence of insomnia as a symptom and did not evaluate the association of insomnia symptom severity with health‐related outcomes among adults with MDD (Asche et al., 2010 ; Bolge et al., 2010 ). We identified one study that examined the relation between insomnia severity and health‐related quality of life (HRQoL) among an MDD population in Switzerland and found that higher insomnia symptom severity was associated with worse HRQoL (Jermann et al., 2021 ). However, that study examined only one aspect of burden, did not control for confounding variables, and was conducted with a clinical population (i.e., those currently seeking care for MDD) in a limited geographical area; the present study attempts to address these gaps.…”
Section: Introductionmentioning
confidence: 99%